2005
DOI: 10.1080/00016350510019946
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some properties of two fiber-reinforced composite materials

Abstract: The results of this study suggest that there are some differences in the tested properties of the FRC materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 19 publications
0
36
0
3
Order By: Relevance
“…Leveraging the advances in adhesive bonding technology, the conservative approach of minimally invasive dentistry allows the esthetics and function of anterior teeth to be restored with adhesive fixed partial dentures. Fueled by increasing interest in metal-free esthetic dentistry, glass fiber-reinforced composite (FRC) has been used in myriad dental applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Of particular interest to this paper are the adhesive fixed partial dentures (AFPDs), which have been favorably reported because of their good clinical performance [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging the advances in adhesive bonding technology, the conservative approach of minimally invasive dentistry allows the esthetics and function of anterior teeth to be restored with adhesive fixed partial dentures. Fueled by increasing interest in metal-free esthetic dentistry, glass fiber-reinforced composite (FRC) has been used in myriad dental applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Of particular interest to this paper are the adhesive fixed partial dentures (AFPDs), which have been favorably reported because of their good clinical performance [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…To reinforce hybrid resin with glass fibers, a bundle of fibers are to be immersed in a resin monomer (bonding agent in this study) and firmly bonded. Previous studies reported that fractures of fiber-reinforced hybrid resins were usually initiated at the interface between the fibers and resin matrix [8][9][10] . It is therefore noteworthy that the bond strength between fibers and resin matrix differs significantly with bonding agents embedded with fibers, whereby the latter is thought to have a significant influence on reinforcing effect.…”
Section: Introductionmentioning
confidence: 99%
“…As with any prosthetic devices, the materials used for fabricating FPDs play a pivotal role in determining the success rate and longevity of these dental restorations. In the case of FRC FPDs, numerous studies were carried out to examine the FRC material from different perspectives: mechanical properties [7][8][9][10] , material development in terms of flexural strength 11) , biocompatibility 12) , fatigue analysis 13,14) , structural analysis in terms of stress distribution 15,16) , and optimal design of FRC framework to obtain the maximum reinforcement effect for FPD 17,18) . Despite the much that is already known about the material properties of FRC framework and particulate-filled composite veneer through the numerous laboratory and clinical studies, much remains to be known about the mechanical behavior of FRC FPDs with respect to displacement and stress magnitude and distribution pattern which were induced during functional loading.…”
Section: Introductionmentioning
confidence: 99%